Chemical characterization of an encapsulated red wine powder and its effects on neuronal cells - Rocha Parra, Diego Fernando (2018)
Red wine polyphenols are known for their implications for human health protection, although they suffer from high instability. For this reason, a red wine powder was prepared by freeze-drying encapsulation in maltodextrin/arabic gum matrix, and its composition was determined by means of high-performance liquid chromatography coupled quadrupole time-of-flight mass spectrometry (HPLC-MS-QTOF). More than thirty polyphenols, including anthocyanins, flavanols, flavonols, phenolic acids and stilbenoids, were identified. Some of the main quantified polyphenols were: malvidin-3-O-glucoside, malvidin 3-O-(6”-acetyl-glucose), petunidin-3-O-glucoside, quercetin-3-O-glucuronide, syringenin-3-O-glucoside, epicatechin, gallic acid and syringic acid. The biological activity of this de-alcoholized and encapsulated red wine on human neuroblastoma SH-SY5Y cells was studied. The results showed that the encapsulated red wine powder has active redox properties, as verified by performing reactive oxygen species (ROS) analysis utilizing a neuronal model. This could help explain its action against the neurotoxicity induced by 6-hydroxydopamine (6-OHDA).